Study of small-scale off-grid photovoltaic aquaponic system for domestic self-consumption application - Au Yong, Wai Tack (2023)
Inflation of food are increasing due to global and local food insecurity. Availability and shortage of food supplies has been evidently affected due to unforeseen global and local events. Therefore, it is sensible to look into alternatives or solutions to secure essential food such as vegetables, especially in urban areas. Relatively big land area is required for conventional home farming. Therefore, it is interesting to study the use of aquaponics farming system as an alternative to tackle the issue described. Considering long-term benefits, and reduce the likeliness to be affected by external factors such as shortage of power supply or increase in power supply cost, the system should be powered by PV system in order to be self-sustained. A small-scale prototype PV Aquaponic (PVA) is to be assembled with minimum cost as a prove-of-concept experiment in this study. Lettuce will be grown to estimate the yield in 3 months. A 300 W PV system with a 3-tier aquaponic planter is found suitable for home growers. The cost of installation, maintenance cost is calculated and yield is recorded. Breakeven period is calculated to be around 4 years based on NPV, LCOE is around RM 3.5 kWh-1 , advantages and disadvantages of the system is discussed.